2001
DOI: 10.1088/0305-4470/34/41/101
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary quantum game

Abstract: We present the first study of a dynamical quantum game. Each agent has a 'memory' of her performance over the previous m timesteps, and her strategy can evolve in time. The game exhibits distinct regimes of optimality. For small m the classical game performs better, while for intermediate m the relative performance depends on whether the source of qubits is 'corrupt'. For large m, the quantum players dramatically outperform the classical players by 'freezing' the game into high-performing attractors in which e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 11 publications
0
35
0
Order By: Relevance
“…If the entangling gate depends upon some parameter, then the classical game can be reproduced when this parameter is set to zero, representing no entanglement. In the present case this is problematic since the entangling gateĴ used by Eisert [4] and others [6,7,15,16,18] does not commute with the classical limit (all phases → 0) ofB, which was Eisert's motivation for the choice ofĴ. Thus this protocol would not reproduce the classical game when the phases are set to zero.…”
Section: A Quantum Parrondo Gamementioning
confidence: 87%
“…If the entangling gate depends upon some parameter, then the classical game can be reproduced when this parameter is set to zero, representing no entanglement. In the present case this is problematic since the entangling gateĴ used by Eisert [4] and others [6,7,15,16,18] does not commute with the classical limit (all phases → 0) ofB, which was Eisert's motivation for the choice ofĴ. Thus this protocol would not reproduce the classical game when the phases are set to zero.…”
Section: A Quantum Parrondo Gamementioning
confidence: 87%
“…Marinatto et al [24] found a unique equilibrium for the Battle of the Sexes game, when entangled strategies were allowed. Later, evolutionarily stable strategies in quantum games and an evolutionary quantum game were also studied by Iqbal et al [25] and Kay et al [26] respectively. Moreover, quantum games have also been implemented using quantum computers [27,28,29].…”
Section: Introductionmentioning
confidence: 98%
“…Hence, classically correlated physical systems (and specially anti-correlated systems) that could provide optimal expected pay-offs, are not allowed for decision-making. However, quantum states such as (4), (7), (8), (9), or those needed to implement all non-trivial vertices guarantee indistinguishability by fundamental laws of physics, while providing at the same time the desired correlations. According to quantum mechanics the quantum state of the N-qubit system is the most complete description of the system, in the sense that it provides the maximum possible information about any future experiments on these qubits.…”
Section: Discussionmentioning
confidence: 99%